ANALISIS E- MARKETING, PROMOSI, DAN INOVASI TERHADAP BRAND AWARENESS SERTA PENGARUHNYA TERHADAP KEPUTUSAN BELI DI ALFAMART (KOTA DENPASAR) - Putra, Adrian Pratama (Jurnal Ecoment Global, 2023)
The purpose of this study is to analyze e-marketing, promotion, and innovation on brand awareness and purchase decisions at Alfamart Denpasar City. Analysis was used with Structural Equation Modeling data techniques with the AMOS program. The conclusion of the analysis results shows that the variables of e-marketing, promotion, innovation and brand awareness have a positive and significant influence on purchasing decisions at Alfamart. Thus, buying interest can influence to increase brand awareness and consumer buying decisions as well as increase the influence of e-marketing on purchasing decisions to further strengthen influence on consumers..